Pengaruh Peran Bahasa Indonesia Dalam Konteks Soal Cerita Matematika - Dina Olivia Nainggolan; Ika Febriana; Combest Prajogo Tambunan; Raja Harly Anugrah Lubis (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
In this research, it was found that mathematical literacy and language literacy have an important role in students' ability to understand and solve mathematical story problems. Language literacy skills, such as the ability to read and understand text, can influence students' ability to solve mathematical problems presented in story form. Improving students' numeracy skills does not only require acceptance of mathematical material, but also the ability to understand and apply mathematical material in everyday life. This shows the importance of students being able to relate mathematical concepts to real situations in everyday life. Mathematical literacy and language literacy are closely related in the context of mathematics story problems. The type of research carried out was descriptive research with literature study. The research method used is a quantitative method by collecting data from previous research and data analysis using the SPSS application. The results of the research show that there is a correlation between Indonesian language literacy and students' mathematical numeracy literacy in solving mathematics story problems. Based on research conducted, Indonesian language scores influence mathematics scores by 54.1%. This proves that Indonesian is very important to learn to expand understanding in solving mathematical story problems. The ability to understand questions/problems of course really depends on the student's reading ability or Indonesian language literacy.